Remarks on the quarrel Leibniz X Newton on the nature of space - Amaral, Lucas Duarte (Cognitio-Estudos: revista eletrônica de filosofia, 2014)
The aim of the present article is to provide some aspects of an important quarrel on the nature of space, namely, the one between Leibniz and Newton. We’ll argue here that there is a necessity in each one of the projects (i.e., the Leibnizian and the Newtonian) for both thinkers to conceive space as they did. On the one hand, Leibniz defended the concept of relative space, which was nothing more than the result of the relation between the positions of things in space; otherwise his thesis of ontological autonomy of the monads would simply fail. Newton, on the other hand, defended the concept of absolute space, which was nothing more than a previous condition enabling the existence of physical bodies; moreover it was an irrevocably prerequisite to the first law of movement.